Pengaruh Labelisasi Halal Mui Pada Produk MakananTerhadap Keputusan Pembelian Mahasiswa Ekonomi & Bisnis Universitas Muhammadiyah Surakarta 2016 - Siregar, Muhammad Rafi, Nurul Huda, M.Ag (2016)
Escalating the amount of food production in Indonesia increases hand in hand with society's demand. For moslem, the determination of halal food is a matter that cannot be tolerated, so it is needed from government institutions that protect its citizen especially for moslem from non-halal food. In Indonesia there is a Research Institute for Food, Drugs and Cosmetics called LPPOM-MUI. This institution was established to ensure the quality of a halal product in Indonesia. If this institution has given label on the product it means that the product is free from illegitimate substance in Islam. Universitas Muhammadiyah Surakarta as an islamic education institution surely will embed islamic behavior in their daily subjects. In this study, the reseacher observed the influence of MUI's halal lable in food products in affecting consumer's decision. The scope of the consumer just focused on the students of Economy and Business Faculties UMS. Field research is done to get the satisfied results. The result of the study is the students of Economy and Business have good knowledge with halal food product and halal labeling from MUI, and it achieved 76,53% students. Thus greatly affect the buying patterns of their consumer products that achieved 69.3% of the total students who can understand the product and the MUI halal labeling